In vitro and In vivo anti-inflammatory activity of leaves of Symplocos cochinchnensis (Lour) Moore ssp laurina - K.S. Lakshmi; Rajendran Vadivu (Bangladesh Pharmacological Society, 2008)
The anti-inflammatory activities of different extracts of leaves Symplocos cochinchnensis Lour ssp laurina (Symplococaceae) were investigated for In-vitro anti-inflammatory activity by human red blood cell membrane stabilization method. The methanol extract showed effective in-vitro anti-inflammatory activity was screened for in-vivo anti-inflammatory activity by carrageenan-induced paw edema in rat model. The potency of the extracts was compared with standard diclofenac (50 mg/kg). The methanol extract showed significant membrane stabilizing action on human red blood cell membrane and reduction of edema in carrageenan induced rat paw edema model.